Cognitive-Behavioral Play Therapy for Preschool Children with Anxiety Disorder Symptoms Related to Moral and Religion: A Single Case Study - Harwiningtyas, Annisa Nur; Yuniarti, Kwartarini Wahyu (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2024)
Anxiety disorder in children requires attention due to its comorbidity with depression. Proper management of this condition is essential. This single case study research explored the effectiveness of cognitive-behavioral play therapy in treating a 6-year-old girl attending an Islamic school who exhibited symptoms of religious anxiety. The client attended a total of 8 intervention sessions. The assessment process involved interviews, observations, and psychological tests, including CPM, Bender-Gestalt, and SCARED for Parents. Pre- and post-intervention results, measured using the SCARED for Parents and unstructured interviews, indicated a reduction in anxiety symptoms, improved coping mechanisms, and changes in maladaptive thinking.